Aklimatisasi dan Respon Pertumbuhan Mutan Leucaena Leucocephala Varietas Tarramba Teradaptasi Asam: Acclimatization and Growth Respond of The Acid-Adapted Mutant of Leucaena leucocephala cv. Tarramba - Muhklisani; Panca Dewi Manuhara Karti; Iwan Prihantoro (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
Acclimatization is the final stage of plant propagation in tissue culture techniques that can determine the success of the nursery process. This study aimed to observe the growth response during the acclimatization stage of the acid-adapted of Leucaena leucocephala Tarramba variety, which developed from tissue culture techniques. The design used in this study was a completely randomized design (CRD) with the cultivation of 11 mutant lines from tissue culture, namely M1-M11 (an acid-adapted mutant from tissue culture addition of 1 ppm IBA) and 2 controls (lamtoro broodstock without gamma irradiation) namely K0 (lamtoro broodstock resulting from tissue culture addition of 0 ppm IBA), K1 (breeding lamtoro from tissue culture addition of 1 ppm IBA). The variables observed were the level of plant viability, plant height, and number of leaves. The results showed that the acclimatization of the plant Leucaena leucocephala to tissue culture production on the M3 and M9 mutant lines gave the best response to plant morphological growth up to 5 WAP (weeks after planting). Key words: acclimatization, IBA hormone, Leucaena leucocephala, tissue culture